Clinical impact of human papillomavirus in laryngeal squamous cell carcinoma: a retrospective study - Chen, Wei-Chih; Chuang, Hui-Ching; Lin, Yu-Tsai; Huang, Chao-Cheng; Chien, Chih-Yen (PeerJ, 2017)
Objectives The purpose of this study is to determine the prevalence and clinical impact of human papillomavirus (HPV) related laryngeal squamous cell carcinoma (LSCC). Methods A total of 106 LSCC patients who underwent primary surgical resection with or without adjuvant radiotherapy/chemoradiotherapy were enrolled retrospectively. Tumors collected from paraffin-embedded samples were used for HPV detection by polymerase chain reaction and in situ hybridization technique. Clinicopathological parameters were recorded for analysis. Results The prevalence of HPV in patients with LSCC was 13.2% in our series and 12 out of 14 (85.7%) HPV-positive tumors were HPV-16. The patients with HPV-positive tumors were older (p = 0.042), less local/regional recurrence (p = 0.037) and non-smoker (p = 0.068). There was no significant difference in the 5-year overall survival (OS) (p = 0.8056) between HPV-positive and -negative tumors. The patients with HPV-positive tumors had a better 5-year disease-specific survival (DSS) (100% vs. 84.8%, p = 0.1485), although the difference did not reach statistical significance. However, the local/regional control rate was significantly better in HPV-positive tumors than in HPV-negative tumors (100% vs. 75%, p = 0.0494). Conclusions A low prevalence of HPV infection in our series suggests that HPV is not a major cause of LSCC. However, a 100% local/regional control rate and DSS were observed in HPV-positive tumors. This finding suggests a different tumor behavior between HPV-positive and HPV-negative LSCC. Further research with a larger sample size is necessary to confirm our observations.
Keywords: HPV; Laryngeal cancer; Survival; Recurrence; Prevalence